Variable Outcome of Immunotherapy in Advanced Multiple Cutaneous Squamous Cell Carcinomas in Two Patients with Recessive Dystrophic Epidermolysis Bullosa - Laura Trefzer; Maria E. Hess; Lena Scholten; Kristin Technau-Hafsi; Frank Meiss; Melanie Boerries; Cristina Has; David Rafei-Shamsabadi (Medical Journals Sweden, 2023)
Cutaneous squamous cell carcinoma (cSCC) is a major complication of recessive dystrophic epidermolysis bullosa (RDEB) that has high morbidity and mortality rates and unmet therapeutic needs. The aim of this study was to evaluate the molecular pattern of cSCC and the clinical course of immunotherapy in 2 RDEB patients with multiple advanced cSCC. Clinical course and disease staging were evaluated retrospectively. The tumour tissues were subjected to immunohistochemical staining. DNA from the blood and cSCC samples was subjected to massive parallel sequencing, and somatic mutations were determined. Patient 1 survived for over 2 years as disease control was achieved with cemiplimab and intralesional interleukin-2. The target advanced cSCC demonstrated a high rate of somatic mutations and strong expression of the immune markers, indoleamine 2,3-dioxygenase, programmed cell death protein ligand 1, and lymphocyte-activation gene 3. The patient ultimately succumbed to complications of oesophageal carcinoma. Patient 2 had an undifferentiated cSCC on the foot, which displayed a low mutational burden and did not express immune markers. The tumour progressed quickly even with cemiplimab therapy. These 2 cases underscore the challenges of cSCC treatment for RDEB. Multiple tumours with different molecular and immune profiles occur concomitantly or sequentially, and surgical excision is not always possible because of the anatomical and tissue constraints imposed by the disease itself. In conclusion, programmed cell death protein 1 inhibitors are approved and effective in treating metastatic and locally advanced cSCC. Our experience and the literature suggest that cemiplimab is an option in patients with RDEB if surgery is not. Somatic mutations and the immune microenvironment should be characterized to predict therapeutic response, particularly in aggressive undifferentiated tumours.